2001
DOI: 10.1002/micr.21801
|View full text |Cite
|
Sign up to set email alerts
|

Effects of some pharmacological agents on the survival of unipedicled venous flaps: an experimental study

Abstract: Clinical and experimental studies have been conducted to improve the survival of venous flaps. As a result of these studies, although various survival mechanisms were raised, none obtained satisfactory information. Venous stasis, and the resultant venous thrombosis, is a factor that decreases the survival of venous flaps. In this study, we evaluated the effects of two antiinflammatory agents, etodolac and etofenamate, on the survival of unipedicled venous flaps. In this study, 35 male New Zealand white rabbits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…The pharmacology of Parnaparin has been extensively investigated in a model of diabetic neuropathy and microangiopathy in rats (21,21), in the survival of venous flaps in rabbits (22), and in a hemodialysis model in dogs (23). In healthy subjects, Parnaparin has been reported to be more active than UFH in the presence of activated platelets (such as may occur in acute coronary syndromes) regardless of whether aspirin is used concomitantly (24).…”
Section: Parnaparinmentioning
confidence: 99%
“…The pharmacology of Parnaparin has been extensively investigated in a model of diabetic neuropathy and microangiopathy in rats (21,21), in the survival of venous flaps in rabbits (22), and in a hemodialysis model in dogs (23). In healthy subjects, Parnaparin has been reported to be more active than UFH in the presence of activated platelets (such as may occur in acute coronary syndromes) regardless of whether aspirin is used concomitantly (24).…”
Section: Parnaparinmentioning
confidence: 99%
“…Yucel and Bayramicli 33 reported significantly improved unipedicled VF survival by using heparin and/or hyperbaric oxygen, although heparin alone did not greatly improve flap survival. Most recently, Askar et al 34 have shown that survival of unipedicled flaps, measuring ‫5.4ן3‬ cm, can be enhanced by systemic delivery of low molecular weight heparin and anti-inflammatory agents. They have concluded that the presence of a venous pedicle was clearly vital for survival in the absence of the artery, and that pharmacologic manipulation can be beneficial in improving flap viability.…”
Section: Discussionmentioning
confidence: 99%